Gender-related Therapeutical Response to Apremilast: New Insights in a Tailored Management of Psoriasis - Emanuele Trovato; Federico Bardazzi; Vito Di Lernia; Monica Corazza; Claudia Lasagni; Francesca Prignano (Dermatology Practical & Conceptual)
Introduction: Psoriasis is a chronic immune-mediated skin condition. One of the intriguing challenges in studying psoriasis has been identification of correlations between this disease and gender and body weight.